Potensi Ancaman Penggunaan Moda Cryptocurrency Crowdfunding dalam Tindak Pidana Pendanaan Terorisme (Terrorist Financing) Menurut Tipologi Freeman dan Davis [The Potential Threat of the Cryptocurrency and Crowdfunding Modes in Terrorist Financing Criminal Act According to Freeman and Davis Typology] - Pratomo, Muhammad Faiq Adi (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2024)
This paper examines the threat of the use of cryptocurrency and crowdfunding, and crowdfunding using cryptocurrency, as a newly emergent threat in terrorist financing. It uses the terrorist funding typologies created by Freeman, supplemented by Davis, to identify the threat presented using these modes of financing. It argues for two conclusions: first, that the use of cryptocurrency adds an added layer of security and reliability to funding sourced by traditional actors, such as state transfers and individual donations by rich donors. Second, the use of crowdfunding allows terrorist organizations, especially those in Southeast Asia, to tap a heretofore untapped market in potential funders, especially at the micro level. Taken together, crowdfunding and cryptocurrency present significant threats to the present Combating the Financing of Terrorism (CFT) regime.Bahasa Indonesia Abstract: Tulisan ini menjelaskan ancaman penggunaan mata uang kripto dan urun dana, serta urun dana dengan menggunakan mata uang kripto sebagai ancaman terbaru dalam dunia pendanaan terorisme. Hal ini menggunakan tipologi pendanaan terorisme yang dibuat oleh Freeman, yang dilengkapi oleh Davis, untuk mengidentifikasi ancaman yang dihadapi dengan menggunakan moda pendanaan tersebut. Tulisan ini memiliki dua kesimpulan argumen. Pertama, penggunaan mata uang kripto menambahkan lapisan keamanan dan keandalan untuk pendanaan yang bersumber dari aktor-aktor tradisional, seperti pendanaan dari negara dan donasi individual dari pendonor yang mapan, Kedua, penggunaan moda urun dana memampukan organisasi terorisme, khususnya yang berpusat di Asia Tenggara, untuk memasuki pasar yang sebelumnya sulit dimasuki oleh donator potensial, terutama di tingkat mikro. Jika digabungkan, urun dana dan mata uang kripto menyediakan ancaman yang signifikan terhadap rezim Combating the Financing of Terrorism (CFT) saat ini.